REAKTUALISASI METODOLOGI PENGAJARAN ISLAM KLASIK DI ERA GLOBALISASI - Sholehuddin, M. Sugeng (Forum Tarbiyah, 2012)
In the history of Islamic education, the golden age of Islam was in the era of Abasyiah. Islamic scholarship progressed very rapidly, since there were supports of the spirit of the Muslims in learning, the caliph, and more importantly, the learning method that was developed in the classical era which was very supportive in the development of Islamic scholarship. The method used in classic era has been able to deliver the muslimstowards the golden era, and that must be appreciated, with re-actualize it in Islamic schools in Indonesia. This is needed to be done since the Islamic education institutions in Indonesia are less able to realize a strong generation in science.